Injustice Disrupted : Experiences of Just Spaces by Victim-Survivors of Sexual Violence - Antonsdóttir, Hildur Fjóla (Social & Legal Studies, 2020)
Given the limitations of the criminal justice system to address cases of sexual violence, feminist scholars are increasingly exploring alternative approaches to justice. Here I ask: What is the role of space in the way victim-survivors of sexual violence can experience justice outside the criminal justice system? Can an understanding of space help us develop justice responses to sexual violence? Interviews were conducted with 35 victim-survivors of sexual violence in Iceland. In cases where offenders remained or re-entered their life space in some way, many participants described feelings of profound fear and anxiety. Participants used a variety of different socio-spatial strategies to ensure that they would not find themselves in the same space as the offenders. Based on the context as well as the networks and mechanisms available to them, these included surrendering, avoiding, negotiating, fighting for, protecting and (re)claiming spaces. Drawing on the concept of the continuum of sexual violence, I suggest that participants’ experiences can be conceptualized on a continuum of injustice. To the degree that participants were able to create what I call just spaces, they gained a sense of belonging, empowerment and freedom, which I suggest can be understood as disrupting this continuum of injustice.